A rare case of an intra-nasal ectopic tooth leading to rhinolith - James, Febin; Sreedharan, Nigil; George, Josmy (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Teeth in non-dentate areas including the intra-sinus and intranasal teeth are rarely encountered in clinical practice. Although the majority of patients remain asymptomatic, the usual presenting complaints are nasal obstruction, epistaxis, hyposmia and headache. In this article, we present a case of an intranasal tooth in a 38-year-old male who presented with complaints of hyposmia and nasal obstruction. Computed tomography (CT) of the paranasal sinuses and nasal cavity showed a tooth-like structure in the left inferior nasal cavity extending from the hard palate. The mainstay of treatment is the surgical removal of the ectopic tooth under anaesthesia. Even in asymptomatic patients, surgical removal of the nasal tooth is advised to prevent complications. Along with a clinician’s understanding of the condition, imaging aids in the diagnosis of an ectopic tooth. Imaging, particularly with CT, also helps plan the surgical approach to treatment.